Strategy and Willingness to Pay for Tourists in a Coastal Tourism Development (A Case Study of Tourism Objects at Baruna Beach, Semarang) - Musliha, Cici; Waridin, Waridin; Suciati, Ika; Febianti, Agatha Risky; Prastiwi, Elisabeth Tyas; Salsabiila, Silvia (Graduate School, Universitas Brawijaya, 2024)
This study aims to estimate the value of tourists' willingness to pay and formulate a strategy for developing Baruna Beach tourism. This study used a mixed-methods approach, utilizing both quantitative and qualitative methods. The quantitative approach employed the contingent valuation method and descriptive statistics, while the qualitative approach utilized SWOT analysis and qualitative descriptive analysis. This study uses primary data. Taken with a questionnaire of 110 tourists and semi-structured interviews conducted with key persons (guards and related agencies). The results showed that as many as 87% of respondents were willing to pay additional costs for developing Baruna tourism. SWOT analysis indicates strong potential for growth, particularly in infrastructure and digital promotion. Integrating WTP with SWOT supports an aggressive strategy focused on environmental conservation, improved facilities, and sustainable revenue generation. This study contributes theoretically by linking economic valuation with strategic tourism management and practically by guiding local authorities in optimizing entrance fees and coastal infrastructure. Findings suggest that digital payment systems for WTP collection, as well as further research on the socio-cultural influences on WTP, are warranted. Despite its insights, the study is limited by accidental sampling, which excludes the perspectives of potential tourists. Future research should explore diverse pricing models and broader market segmentation for sustainable coastal tourism.